GEOMETRIES, ATOM IN MOLECULE, AND NATURAL BOND ORBITAL ANALYSES OF E2H2, E2H2AuCl, E2H2(AuCl)2 COMPOUNDS (E = N–Bi). A CHALLENGE FOR THE SKILLS OF SYNTHETIC CHEMISTS - Ai Nhung, Nguyen Thi; Ly, Nguyen Van; Dien, Do; Tat, Pham Van (Vietnam Journal of Science and Technology, 2014)
The bonding in and stability of dimeric group 15-compounds of the general formula E2R2 has been investigated in the past mainly with E = N, P and R = H, Me. In this study, we extend these investigations to all group 15-elements E and analyze the character of the E-E bond for E2H2 compounds with the aid of atoms in molecule-AIM and natural bond orbital -NBO. We carried out a comprehensive-theoretical investigation of covalent E2H2 compounds and the changes in bonding electron density upon mono- and di-auration. The theoretical results presented in this study clearly show that the N-N bond in N2H2 gets longer upon complexation with AuCl while the P-P-, As-As-, Sb-Sb- and Bi-Bi-bonds contract, although the E-E bond orders and dissociation energies decrease upon auration. The condition of a negative total energy (H(r) < 0) in the bonding region holds for all studied covalent bonds of all molecules in the AIM analysis. At the time the data give as useful for understanding and concluding the chemical bonding behavior of E2H2 compounds in group-15 upon mono- and di-auration